Perjuangan Perempuan Menghadapi Kekuasaan Dalam Lakon â€œSusi Duyungâ€: Ludruk Budhi Wijaya - M. Shoim Anwar; Listyo Ambarwati (Jurnal Budaya Nusantara, 2017)
Ludruk Budi Wijaya Group is a cultural actor who is active in maintaining and developing the arts of thepeople. The characteristic of ludruk as a critical stage art is maintained, including the structure of the show. Ludruk isa channel for the aspirations of the little people and represents their lives. The "Susi Duyung" play performed byLudruk Budhi Wijaya is also related to the lives of the low society, the fishermen in Ngliyep Village who areoppressed economically by the authorities. The presence of Susi's character as a hero is a modeling that injustice must beresisted. Women should not be underestimated and should be given equal opportunities with men in the fight. Becauseof his firm and courageous attitude, with the public, Susi's character strugled persistently for social justice and erasedfor political corruption so that he is appointed leader.